A composite phase change material for ultra-high specific energy battery pack suitable for near-space environment

By using composite phase change materials in ultra-high specific energy battery packs, the problem of uneven temperature distribution within the battery pack in the near space environment is solved, and the temperature gradient is reduced and the battery performance is improved.

CN117903757BActive Publication Date: 2025-04-04TIANJIN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410082317.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-19
Publication Date
2025-04-04
Estimated Expiration
2044-01-19

AI Technical Summary

Technical Problem

In the near space environment, the internal temperature distribution of energy storage batteries is uneven due to charging and discharging, resulting in a single cell with a specific energy of 600Wh/kg being affected by the temperature gradient, resulting in differences between individuals, affecting battery performance and cycle life.

Method used

A composite phase change material is used, which consists of phase change material (animal oil and calcium chloride hexahydrate), pore-forming agent (sodium bicarbonate, sodium carbonate, citric acid) and functional enhancers (beryllium oxide, alumina, aluminum nitride, boron nitride, silicon nitride, silicon carbide). A porous structure is formed by vacuuming to reduce the difference in the temperature gradient of the ultra-high specific energy battery pack.

Benefits of technology

It effectively reduces the temperature difference inside the ultra-high specific energy battery pack, improves the cycle life and specific energy of the battery pack, and ensures stable operation in the near space environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117903757B_ABST
    Figure CN117903757B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of secondary chemical power sources, specifically a composite phase change material for ultra-high specific energy battery packs suitable for near-space environments, and discloses for the first time a method for long-term temperature control of ultra-high energy density battery packs in an external environment of about 90°C and 1700 Pa. By selecting suitable phase change materials, pore formers, and function-enhancing agents to form porous composite phase change materials, the present invention overcomes the problem of inconsistent battery performance caused by uneven temperature distribution in ultra-high energy density lithium battery packs above 400Wh / kg in low-temperature and low-pressure environments, prolongs the cycle life of ultra-high energy density lithium battery packs, and provides long-term and effective endurance time for all-electric aircraft operating in near-space.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary chemical power sources, and in particular relates to a composite phase change material for an ultra-high specific energy battery pack suitable for a near-space environment. Background Art

[0002] Near-space refers to a space region with an altitude of 20km-100km. The air here is thin. It is located at the junction of the atmosphere and space, and is between the flight space of ordinary aircraft and the orbital space of spacecraft. In this area, conventional aircraft cannot fly up and satellites cannot land. Both ground-based and space-based observations have their own shortcomings. Currently, only high-altitude scientific balloons can operate stably and for a long time, and there is a lack of rich and effective long-term in-situ detection methods. Based on the above situation, the concept of near-space aircraft equipment has also been developed, which refers to aircraft that use near-space to destroy and interfere with space targets (more than 100km from the ground) and implement communications, telemetry, reconnaissance, transportation, interception and attack on land, sea and air targets.

[0003] Near-space aircraft can provide more information, are relatively cheaper than satellites, and have longer working hours than ordinary aircraft. In the civilian field, near-space aircraft can focus on environmental monitoring of a certain area for a long time. Compared with satellites that are limited by orbit and speed, their monitoring is more sensitive and accurate. However, energy storage batteries used in this area will face the problem of low temperature and low air pressure. For example, at an altitude of 20km, the air pressure will drop to 5470Pa and the temperature will drop to -57℃. When the altitude continues to rise to 30km, the air pressure will drop to 1200Pa, which is infinitely close to a vacuum.

[0004] For heat preservation, thermal insulation materials such as aerogel can be used to effectively isolate the external temperature exchange, because under low pressure, convection behavior has been greatly weakened, and there is no corresponding release surface for behaviors such as heat conduction to propagate. In addition, the only remaining radiation propagation path can also be isolated by wave-absorbing and reflective coatings. Therefore, compared with how to keep warm, the inventors found through low-temperature and low-pressure experiments that the real difficulty lies in how to control the uneven internal temperature distribution of energy storage batteries caused by charging and discharging in a highly independent and insulated system, especially in the area near the outer edge of the battery pack. From the perspective of heat transfer, because heat exchange occurs first, it is bound to be lower than the temperature in the middle area of ​​the battery pack. The emergence of an internal temperature gradient field will cause the single cell with a specific energy of 600Wh / kg to be affected by the temperature gradient, resulting in differences between individuals, because the ionic conductivity increases with the increase of temperature, and the battery performance in the middle and at both ends will be increasingly affected by temperature as the number of cycles increases.

[0005] Invention patent CN109802196A discloses a battery rapid heating device of hydrated salt phase change material, comprising: a cavity, a plurality of batteries arranged in the cavity, and a phase change material filled in the cavity and directly wrapping the batteries, wherein the phase change material is an inorganic hydrated salt; the opening of the cavity is sealed by a top cover and a rubber sealing strip, and a latent heat release device is arranged at the bottom of the cavity to trigger the solidification process of the phase change material to release latent heat to rapidly heat the battery.

[0006] Invention patent CN102268245A discloses a method for preparing room temperature inorganic phase change material, comprising the following steps:

[0007] (1) heating calcium chloride or its hydrate at 50°C to 80°C to completely melt and prepare a 50% calcium chloride solution; (2) adding a modifier, bischofite, under stirring, to prepare a brine compound containing 0% to 33% of bischofite; (3) adding a nucleating agent in an amount of 2% to the brine compound, and reheating until the brine compound is melted into a uniform fluid state; (4) crystallizing the uniform fluid brine compound at a low temperature of 10°C, and then melting it at 30°C to 40°C and pouring it into a container for packaging.

[0008] However, in current technology, there is no temperature control technology for energy storage batteries in near-space low-temperature and low-pressure environments. In particular, phase change materials themselves are highly flexible and plastic, making them easy to install and use. They do not need to be pre-packaged in a sealed frame to achieve phase change energy storage, because the sealed frame will rupture and fail under long-term low pressure. Summary of the invention

[0009] To fill the gap in the prior art, the present invention proposes a composite phase change material for an ultra-high specific energy battery pack suitable for a near-space environment to reduce the difference in temperature gradient inside the ultra-high specific energy battery pack in a near-space environment.

[0010] The objective of the present invention is achieved through the following technical solutions:

[0011] The present invention provides a composite phase change material, which is a porous material in the use state, and its main components are composed of phase change material, pore forming agent, and function increasing agent; the main components of the phase change material are animal oil and calcium chloride hexahydrate. The composite phase change material has no pores before it is not used, and its pores are realized by vacuuming during application. The application environment is a low pressure environment not higher than 10000pa; such as a near-space environment.

[0012] As an embodiment of the present invention, the phase change temperature range of the composite phase change material is 25°C to 40°C.

[0013] As an embodiment of the present invention, the pore-forming agent is at least one of sodium bicarbonate, sodium carbonate and citric acid.

[0014] As an embodiment of the present invention, the functional enhancing agent is at least one of beryllium oxide, aluminum oxide, aluminum nitride, boron nitride, silicon nitride, and silicon carbide.

[0015] As an embodiment of the present invention, the animal oil is at least one of lard, sheep oil, beef tallow, fish oil, bear oil, camel oil, horse oil, donkey oil, dog oil and cat oil.

[0016] As an embodiment of the present invention, the mass proportions of the phase change material, the pore former and the function increasing agent in the composite phase change material are 20% to 98.5%, 0.5% to 35% and 1% to 45% respectively.

[0017] As an embodiment of the present invention, the mass ratio of animal oil to calcium chloride hexahydrate in the phase change material is 1:0.1-9.

[0018] The present invention also relates to a use of a composite phase change material as a composite phase change material for an ultra-high specific energy battery pack in a near-space environment, wherein the composite phase change material is used to control the temperature of the battery pack, specifically to reduce the difference in temperature gradient inside the ultra-high specific energy battery pack in a near-space environment.

[0019] As an implementation example, the composite phase change material is filled in the internal cell space gaps of the battery pack to perform temperature control on the battery pack.

[0020] As an embodiment of the present invention, the composite phase change material in a solidified state is heated to form a paste-like gel, which is slowly injected into the internal cell space gap of the battery pack; it is solidified into a solid at room temperature, and then the battery pack is placed in a low pressure environment of no more than 2000 Pa for at least 1 hour to obtain a porous composite phase change material. In some embodiments, the battery pack is placed in a low pressure environment of no more than 2000 Pa for 1 to 6 hours.

[0021] As an embodiment of the present invention, the heating temperature is 30°C to 45°C.

[0022] As an embodiment of the present invention, the energy density of the ultra-high specific energy battery pack for the near-space environment is not less than 400Wh / kg.

[0023] The present invention also relates to a method for preparing a composite phase change material, the method comprising the following steps:

[0024] S1, heating the phase change material to 40°C to 80°C, and after it is completely melted into liquid, quickly adding a pore-forming agent and a function-enhancing agent, and continuously stirring to obtain a solid-liquid mixed composite phase change material;

[0025] S2. Rapidly cool the solid-liquid mixed composite phase change material to below 20° C. to obtain a completely solidified composite phase change material.

[0026] As an embodiment of the present invention, in step S1, the phase change material is placed in a container for heating. The container is made of polytetrafluoroethylene, para-polyphenylene, ceramic or metal.

[0027] In some embodiments, in step S2, the solid-liquid mixed composite phase change material is rapidly cooled to below 20°C within 10 minutes.

[0028] As an embodiment of the present invention, in the above preparation method, all steps need to be carried out under the condition of humidity <3%.

[0029] Compared with the traditional room temperature phase change material, the present invention introduces the concept of bionics for the first time to modify the phase change material. In order to solve the problem that the internal battery of the near-space environment battery pack actually needs to be in a room temperature environment of 25-40°C for a long time, the animal oil with a similar phase change temperature is reasonably formulated to obtain a flexible phase change material substrate. In addition, calcium chloride hexahydrate is an inorganic solid powder with a phase change temperature of 29°C, but it is very easy to absorb water, so it is generally not a phase change material alone. It is usually necessary to seal it in a separate sealed container to isolate it from air contact. The present invention does not need to set up an additional container, and it can be prepared into any shape by relying on lard and bio-oil derivatives, which is more convenient to fit with the internal battery cells of the ultra-high specific energy battery pack. By introducing bio-oil with a phase change temperature close to it, it can be effectively coated on the surface of its particles. The lard, sheep oil, beef tallow, fish oil, bear oil, camel oil, horse oil, donkey oil, dog oil, and cat oil cited in the present invention all have good hydrophobicity through reasonable formulation, thereby effectively isolating the moisture absorption of calcium chloride hexahydrate from a microscopic point of view. Bio-oil and calcium chloride hexahydrate only have the characteristics of room temperature phase change materials, but they cannot be used in near-space environments because they still face the problem of low air pressure. The overly sealed bio-oil and calcium chloride hexahydrate are very likely to be deformed and damaged during the process of reducing air pressure due to changes in internal and external air pressure, thereby reducing its phase change insulation effect. Therefore, the concept of pore formers is introduced into phase change materials to make phase change materials into porous phase change materials. The chemical mechanism equation for the pores generated by the pore former is shown in Equation 1-3:

[0030] 1. 2C6H8O7+3Na2CO3→2Na3C6H5O7+3CO2↑+3H2O (1)

[0031] 2. C6H8O7+3NaHCO3→Na3C6H5O7+3CO2↑+3H2O (2)

[0032] 3.2NaHCO3(heating)→2NaCO3+CO2↑+H2O(3)

[0033] Among them, CO2 as a gas is confined in a mixture of bio-oil with high viscosity and calcium chloride hexahydrate, and will not react with it. H2O is rejected by the bio-oil and can easily separate oil and water. Na3C6H5O7 (sodium citrate) and NaCO3 have certain anti-corrosion properties and can reduce the formation of mold. The present invention cleverly introduces gas into the liquid phase change material through basic chemical principles, and these gases can be removed by vacuuming during use, and at the same time, they are attached to the surface of the battery cell inside the battery pack in situ to achieve the purpose of phase change temperature control.

[0034] In addition, because the calcium chloride hexahydrate used in the present invention is a strong acid weak base salt, and the sodium bicarbonate and its byproduct sodium carbonate in the pore-forming agent are strong base weak acid salts, theoretically the two will react, but because the present invention cleverly uses pork and animal oil derivatives as coating solvents, which are evenly covered on the surface of the solid particle powder in the present invention, in addition to the phase change heat storage effect of the pork and animal oil derivatives themselves, they also isolate the interface reaction process of calcium chloride hexahydrate and other substances, that is, lacking water as an intermediate reaction medium, even if the strong acid weak base salt and the strong base weak acid salt are in direct contact, no reaction will occur.

[0035] Finally, relying solely on the above-mentioned porous room temperature phase change material cannot solve the thermal conductivity temperature of the battery pack in the near-space environment, because the above-mentioned material only has the phase change heat storage function, but lacks the thermal conductivity. In the battery pack, in order to avoid leakage of high-voltage batteries, the insulation requirements are very high, so metal or carbon materials cannot be used as heat-conducting carriers. The inventor introduced heat-conducting insulating material powder into the above-mentioned material according to the authorized invention patent CN108963291B "A thin thermal battery with independent electrode system and heating system", such as thermal conductivity of 32-400W / (m·K) and resistivity greater than 10 15 The composite material composed of one or more of Ω·cm beryllium oxide, aluminum oxide, aluminum nitride, boron nitride, silicon nitride, and silicon carbide as a functional additive greatly improves the thermal conductivity of the above phase change material, and the pores of these thermally conductive insulating materials also have a capillary adsorption effect, which can further limit the fluidity of the phase change material and better keep it in a paste at the phase change temperature.

[0036] Therefore, compared with the prior art, the present invention has the following beneficial effects:

[0037] 1) The present invention proposes a new room-temperature phase change material with a phase change temperature point near room temperature, and endows it with porous properties through a pore-forming agent, so that it can cope with the low air pressure problem in the near space, and the pore-forming agent also has an anti-corrosion effect.

[0038] 2) All materials of the present invention are systematically integrated by the inventor through basic chemical principles, starting from the concept of bionics. Different from the technical means of introducing multi-component phase change materials into traditional composite phase change materials to reduce the eutectic melting point, the present invention directly adopts two types of materials with different properties and similar phase change temperatures for common heat storage, and cleverly uses bio-oil to overcome the moisture absorption problem of calcium chloride hexahydrate. At the same time, calcium chloride hexahydrate is used to react with bio-oil to overcome the problem that bio-oil may be deteriorated due to long-term exposure to the near-space radiation environment due to space radiation, thereby improving its service life in near-space.

[0039] 3) The bio-oil introduced in the present invention as a phase change substrate also gives the final phase change material a good plastic and flexible structure, which can be more conveniently filled in the gaps of the battery cells inside the ultra-high energy density lithium battery pack, achieving the integration of structural functions of both heat storage and supporting structure.

[0040] 4) The present invention aims at the insulation requirements of electronic components and currents inside near-space ultra-high specific energy battery packs, while overcoming the problem of slow thermal conductivity in traditional phase change materials. It introduces thermally conductive insulating materials such as beryllium oxide, aluminum oxide, aluminum nitride, boron nitride, silicon nitride, and silicon carbide to more effectively solve the problem of thermal conduction of composite phase change materials in high-voltage, ultra-high specific energy batteries without affecting their insulation safety.

[0041] 5) The porous bionic composite phase change material created for the first time in this invention can effectively reduce the temperature difference inside the ultra-high specific energy battery pack for the low temperature and low pressure environment of near space. Figure 2 , the temperature gradient can be reduced from 7.3℃ to 0.2℃ at -90℃, 1700Pa, and the temperature gradient can be reduced from the maximum 5℃ to 0.5℃ in long-term cycles at -70℃, 7000Pa. By reducing the impact of temperature differences, the consistency of single cells in ultra-high specific energy battery packs used in near-space environments is greatly improved, thereby improving the overall cycle life and specific energy of the battery pack. For details, see Figure 4 The experimental results show that it has great engineering application mechanism.

[0042] 6) Compared with the disclosed room temperature phase change materials, the present invention does not require an additional cavity or frame to encapsulate the phase change material for use. It is highly flexible and plastic, and can be changed into any shape when heated to a paste state, so that it can fit tightly on the surface of the battery cell inside the battery pack. It also cleverly solves the problem that the main components of the phase change material used, such as animal oil and calcium chloride hexahydrate, become liquids and flow freely when there is no frame or cavity. This avoids the current situation that pure animal oil and calcium chloride hexahydrate are not suitable for low pressure environments and are prone to leakage. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0044] Figure 1 It is the DSC test curve diagram of Example 1 in the present invention;

[0045] Figure 2 The temperature change curve of the ultra-high specific energy battery pack of Application Example 1 and Comparative Example 1 of the present invention after being placed in an environment of -90°C and 1700Pa for 5 hours;

[0046] Figure 3 It is a temperature change curve diagram of multi-point temperature measurement inside the ultra-high specific energy battery pack of Application Example 1 and Comparative Example 1 of the present invention in an environment of -70°C and 7000Pa;

[0047] Figure 4 It is a charge and discharge performance curve diagram of the ultra-high specific energy battery pack of Application Example 1 and Comparative Example 1 of the present invention in an environment of -70°C and 7000Pa.

[0048] Figure 5 This is a spatial schematic diagram of a typical phase change material in the present invention before and after being injected into an ultra-high specific energy battery pack. DETAILED DESCRIPTION

[0049] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0050] Example 1

[0051] A method for preparing a composite phase change material for an ultra-high specific energy battery pack suitable for near-space environment comprises the following steps:

[0052] Step 1: According to the proportions in Table 1, weigh a total of 50 g of the composite phase change material.

[0053] Table 1 Composite phase change material formula 1

[0054]

[0055] Step 2: In an environment with a humidity of 1%, put the calcium chloride hexahydrate in step 1 into a stainless steel cup-shaped container and start stirring. After the temperature rises to 55°C, add another phase change material of equal mass, lard, and after it is completely melted into liquid, quickly add sodium bicarbonate powder and boron nitride powder, and continue stirring to obtain a solid-liquid mixed composite phase change material. After stirring until bubbles appear in the solid-liquid mixture, stop stirring within 5 minutes.

[0056] Step 3: The solid-liquid mixed composite phase change material in step 2 is quickly placed in a -5°C freezer to obtain a fully solidified composite phase change material, the DSC test curve of which is shown in the figure below: Figure 1 shown.

[0057] Afterwards, the cured composite phase change material obtained in step 3 is heated to 35° C. to make it into a paste-like gel, which is then slowly injected into the internal cell space gap of the ultra-high-energy battery pack (such as Figure 5 ), and then wait for it to solidify into a solid at 25°C, and then place the battery pack in a low-pressure environment of 1700 Pa for 1 hour to obtain a porous composite phase change material. Figure 1 is the DSC test curve diagram of this embodiment, Figure 1 It can be seen that the phase change enthalpy value of the phase change material is as high as -128.62 J / g, that is, 1g of the composite phase change material can store 128.62 J / g of heat and begins to absorb and store heat between 25.7 and 40°C.

[0058] Example 2

[0059] A method for preparing a composite phase change material for an ultra-high specific energy battery pack suitable for near-space environment comprises the following steps:

[0060] Step 1: According to the proportions in Table 2, weigh a total of 100 g of the composite phase change material.

[0061] Table 2 Composite phase change material formula 2

[0062]

[0063] Step 2: In an environment with a humidity of 1%, put the calcium chloride hexahydrate in step 1 into a stainless steel cup-shaped container and start stirring. After the temperature rises to 60°C, put in another phase change material, a mixture of lard and butter (mixed in a weight ratio of 1:3) with a mass twice that of the mixture. After it is completely melted into a liquid, quickly add the pre-prepared mixture of sodium carbonate and citric acid (prepared according to the molar ratio of equation 1) and aluminum nitride powder, and continue stirring to obtain a solid-liquid mixed composite phase change material. After stirring until bubbles are generated in the solid-liquid mixture, stop stirring immediately.

[0064] Step 3: quickly put the solid-liquid mixed composite phase change material in step 2 into a freezer at 0°C for quick freezing to obtain a completely solidified composite phase change material.

[0065] Afterwards, the cured composite phase change material obtained in step three is heated to 35°C to make it into a paste-like gel, which is slowly injected into the internal cell space gaps of the ultra-high-energy battery pack, and then allowed to solidify into a solid at 25°C. The battery pack is then placed in a low-pressure environment of 7000 Pa for 2 hours to obtain a porous composite phase change material.

[0066] Example 3

[0067] A method for preparing a composite phase change material for an ultra-high specific energy battery pack suitable for near-space environment comprises the following steps:

[0068] Step 1: According to the proportions in Table 3, weigh a total of 100 g of the composite phase change material.

[0069] Table 3 Composite phase change material formula three

[0070]

[0071] Step 2: In an environment with a humidity of 1%, put the calcium chloride hexahydrate in step 1 into a polytetrafluoroethylene cup-shaped container and start stirring. After the temperature rises to 45°C, put in another phase change material lard and sheep fat mixture (mixed in a weight ratio of 1:1) with a mass of 1.5 times its mass. After it is completely melted into a liquid, quickly add the pre-prepared sodium bicarbonate and citric acid mixture (prepared according to the molar ratio of equation 2), aluminum nitride, boron nitride, and aluminum oxide powder (mixed in a mass ratio of 1:1:1), continue stirring, and obtain a solid-liquid mixed composite phase change material. After stirring until bubbles are generated in the solid-liquid mixture, stop stirring immediately.

[0072] Step 3: quickly put the solid-liquid mixed composite phase change material in step 2 into a 5° C. freezer to obtain a completely solidified composite phase change material.

[0073] Afterwards, the cured composite phase change material obtained in step three is heated to 32°C to make it into a paste-like gel, which is slowly injected into the internal cell space gaps of the ultra-high-energy battery pack, and then allowed to solidify into a solid at 20°C. The battery pack is then placed in a low-pressure environment of 1700 Pa for 1 hour to obtain a porous composite phase change material.

[0074] Application Example 1

[0075] Ultra-high energy density lithium battery cells are prepared using the technology of authorized invention ZL202111063559.5. The overall battery design scheme can use high nickel ternary positive electrode (commercially available), metal lithium negative electrode and electrolyte in ZL202111063559.5. The specific energy of the battery cell is 570Wh / kg at 0.2C, the battery cell capacity is 22Ah, 48 of the battery cells are connected in series, and the battery cell mass is about 7kg. Aluminum-magnesium alloy is used as the battery cell frame to fix it, 1cm thick aerogel is attached around the aluminum-magnesium alloy plate, and then a carbon fiber plate is attached to the outside of the aerogel as a supporting frame. The composite phase change material in Example 1 is heated and injected into the gap between the battery cell and the aerogel. A porous composite phase change material is obtained according to the method in Example 1. The total mass of the battery pack is 7.9kg. The battery pack includes a single battery cell, a power management system, a frame, a thermal insulation material, a phase change material, a connecting line and a device. The ultra-high energy density battery with porous composite phase change material was placed in a -70°C, 7000Pa environment for charge and discharge cycles. The overall initial specific energy of the battery pack was 490Wh / kg, and the specific energy after 30 cycles was 427.3Wh / kg.

[0076] Comparative Example 1

[0077] Ultra-high energy density lithium battery cells are prepared using the technology of authorized invention ZL202111063559.5. The overall battery design scheme can use high nickel ternary positive electrode (commercially available), metal lithium negative electrode and electrolyte in ZL202111063559.5. The specific energy of the battery cell is 570Wh / kg at 0.2C, the battery cell capacity is 22Ah, 48 of the battery cells are connected in series, and the mass of the battery cell is about 7kg. Aluminum-magnesium alloy is used as the battery cell frame to fix it, 1cm thick aerogel is attached around the aluminum-magnesium alloy plate, and then a carbon fiber plate is attached to the outside of the aerogel as a support frame. The total mass of the battery pack is about 7.8kg, and the battery pack includes a single battery cell, a power management system, a frame, insulation materials, connecting lines and devices. The ultra-high energy density battery is placed in a -70℃, 7000pa environment for charge and discharge cycles. The overall initial specific energy of the battery pack is 484.1Wh / kg, and the specific energy after 30 cycles is 346.5Wh / kg.

[0078] Figure 2 The temperature change curves of the ultra-high specific energy battery packs of Application Example 1 and Comparative Example 1 after being placed in an environment of -90°C and 1700 Pa for 5 hours; Figure 3 The temperature variation curves of the ultra-high specific energy battery pack of Application Example 1 and Comparative Example 1 at -70°C and 7000Pa are shown; Figure 2 , 3It can be seen that the porous bionic composite phase change material of the present invention can effectively reduce the temperature difference inside the ultra-high specific energy battery pack. In the same time period, the temperature gradient can be reduced from 7.3°C to 0.2°C at -90°C and 1700Pa, and the temperature gradient can be reduced from a maximum of 5°C to 0.5°C in a long-term cycle at -70°C and 7000Pa.

[0079] Figure 4 The charge and discharge performance curves of the ultra-high specific energy battery pack of Application Example 1 and Comparative Example 1 in an environment of -70°C and 7000Pa are shown; Figure 4 It can be seen that Application Example 1 greatly improves the consistency of single cells of the ultra-high specific energy battery pack used in a near-space environment by weakening the influence of temperature differences, thereby improving the overall cycle life and specific energy of the battery pack.

[0080] In summary, the present invention discloses for the first time how to perform temperature control on ultra-high energy density battery packs in an external environment of -90°C and about 1700pa for a long time. By selecting suitable phase change materials, pore formers, and function increasers to form porous composite phase change materials, the present invention overcomes the problem of inconsistent battery performance caused by uneven temperature distribution in ultra-high energy density lithium battery packs above 400Wh / kg in low temperature and low pressure environments, prolongs the cycle life of ultra-high energy density lithium battery packs, and provides long-term and effective endurance time for all-electric aircraft operating in near-space.

[0081] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A composite phase change material, characterized in that: The composite phase change material is non-porous before use, and is a porous material in the use state, and its pores are realized by vacuuming during use, and the application environment is a near-space environment; the composite phase change material mainly consists of a phase change material, a pore-forming agent, and a function-increasing agent; the main components of the phase change material are animal oil and calcium chloride hexahydrate; the pore-forming agent is sodium bicarbonate, or a combination of at least one of sodium bicarbonate and sodium carbonate and citric acid; the function-increasing agent is at least one of beryllium oxide, aluminum oxide, aluminum nitride, boron nitride, silicon nitride, and silicon carbide; the animal oil is at least one of lard, sheep oil, beef tallow, fish oil, bear oil, camel oil, horse oil, donkey oil, dog oil, and cat oil; the mass proportions of the phase change material, the pore-forming agent, and the function-increasing agent in the composite phase change material are 20% to 98.5%, 0.5% to 35%, and 1% to 45%, respectively; the mass ratio of animal oil to calcium chloride hexahydrate in the phase change material is 1:0.1 to 9; The composite phase change material is prepared by a method comprising the following steps: S1, heating the phase change material to 40°C-80°C, and after it is completely melted into liquid, adding a pore-forming agent and a function-enhancing agent, and continuously stirring to obtain a solid-liquid mixed composite phase change material; S2. Rapidly cool the solid-liquid mixed composite phase change material to below 20° C. to obtain a completely solidified composite phase change material.

2. The composite phase change material according to claim 1, characterized in that: The phase change temperature range of the composite phase change material is 25°C to 40°C.

3. Use of the composite phase change material according to claim 1 or 2 as a composite phase change material for ultra-high specific energy battery packs in near-space environments, characterized in that: The composite phase change material is used to control the temperature of the battery pack.

4. The use according to claim 3, characterized in that The composite phase change material in a solidified state is heated to form a paste-like gel, and then injected into the internal cell space gap of the battery pack; it is allowed to solidify into a solid at room temperature, and then the battery pack is placed in a low pressure environment of no more than 2000 Pa for at least 1 hour to obtain a porous composite phase change material.

5. The use according to claim 3, characterized in that: The energy density of the ultra-high specific energy battery pack for the near-space environment is not less than 400Wh / kg.

Citation Information

Patent Citations

  • A method for preparing room temperature inorganic phase change materials

    CN102268245A

  • A thin thermal battery with independent electrode and heating systems

    CN108963291B

  • Rapid battery heating device with hydrated salt phase change material

    CN109802196A

  • Lithium electrolyte of solvent self-sacrifice in-situ protection electrode, preparation and application thereof

    CN113782810A

  • Preparation method of phase change material with energy storage and composite network structure

    CN115584242A